PENGEMBANGAN MEDIA PEMBELAJARAN PERMAINAN TEKA-TEKI SILANG PADA MATA PELAJARAN SEJARAH KELAS X IPA SMA N 8 KOTA JAMBI - Mohammad Andi Wasgito, Nada tismaliya sari, (Universitas Batanghari Jambi, 2020)
AbstractThis research and development departs from the problems that occur in SMA N 8 in the city of Jambi where the learning is monotonous and less varied so that students get bored quickly. Learning media can be an alternative in solving problems that occur. This research aims to produce instructional media products, namely crossword puzzles and apply it to history lessons in class X IPA at SMA N 8, Jambi city. The research method used in this research is ADDIE developed by Lee and Owen which has five stages, namely; 1) analysis, 2) design, 3) development, 4) implementation, and 5) evaluation. In the implementation stage, the researcher adopted the Martin Tessmen model. The research was conducted at SMA N 8 Kota Jambi with research subjects of class X IPA students, amounting to 2 people for individual trials, 10 people for small group trials, and 34 people for large group trials. From the results of field trials, it was found that the results of individual trials, the total score an average percentage of 82.6% were included in the